A case control study of HPV and abnormal cervical cytology among HIV infected and non infected females. - Karmacharya, Kavita; Batra, Rajiv; Kandasamy, Subramaniam (Medical Journal of Shree Birendra Hospital, 2017)
Introduction: HPV is a known cause of abnormal cervical cytology and cervical cancer. The prevalence of cervical cancer among HIV infected women is higher. This study compared the prevalence of HPV and abnormal cervical cytology between HIV positive and negative females. Methods: In this case-control study, 100 consecutive HIV-positive females were included as cases and 75 HIV-negative females were taken as controls. Cervical smears and scrapes were taken for Pap smear and HPV DNA by PCR and compared. Results: Prevalence of HPV among HIV-positive females (35%; n=35) was higher than HIV-negatives (8%; n=6) and was statistically significant (<0.05). The incidence of LSIL, HSIL and ASCUS in the HIV-positive was 16%, 3%, 2% respectively and 5%, 2.5%, 1.3% respectively in the HIV-negative. LSIL lesion showed statistical significance (p <0.05) but HSIL and ASCUS lesions had no such significance (p values 0.65 and 0.56 respectively). Conclusions: A strong correlation was found between HPV positivity and abnormal cervical lesions diagnosed on cytology, especially among the HIV positive population especially LSILs. Therefore, screening of cervical cancer should include HPV identification and cervical cytology, especially among HIV positive women, so that prompt and appropriate treatment of HIV would help in reducing the prevalence of cervical cancer.